Demographic Differences in Catheter Ablation After Hospital Presentation With Symptomatic Atrial Fibrillation. Issue 9 (22nd September 2015) - Kummer, Benjamin R.; Bhave, Prashant D.; Merkler, Alexander E.; Gialdini, Gino; Okin, Peter M.; Kamel, Hooman
Abstract : Background: Catheter ablation is increasingly used for rhythm control in symptomatic atrial fibrillation (AF), but the demographic characteristics of patients undergoing this procedure are unclear. Methods and Results: We used data on all admissions at nonfederal acute care hospitals in California, Florida, and New York to identify patients discharged with a primary diagnosis of AF between 2006 and 2011. Our primary outcome was readmission for catheter ablation of AF, identified using validated International Classification of Diseases, Ninth Revision, Clinical Modification procedure codes. Cox regression models were used to assess relationships between demographic characteristics and catheter ablation, adjusting for Elixhauser comorbidities. We identified 397 612 eligible patients. Of these, 16 717 (4.20%, 95% CI 0.41 to 0.43) underwent ablation. These patients were significantly younger, more often male, more often white, and more often privately insured, with higher household incomes and lower rates of medical comorbidity. In Cox regression models, the likelihood of ablation was lower in women than men (hazard ratio [HR] 0.83; 95% CI 0.80 to 0.86) despite higher rates of AF‐related rehospitalization (HR 1.23; 95% CI 1.21 to 1.24). Compared to whites, the likelihood of ablation was lower in Hispanics (HR 0.60; 95% CI 0.56 to 0.64) and blacks (HR 0.68; 95% CI 0.64 to 0.73), even though blacks had only a slightly lower likelihood of AF‐related rehospitalization (HR 0.97; 95% CI 0.94 to 0.99) and a higher likelihood of all‐cause hospitalization (HR 1.38; 95% CI 1.37 to 1.39). Essentially the same pattern existed in Hispanics. Conclusions: We found differences in use of catheter ablation for symptomatic AF according to sex and race despite adjustment for available data on demographic characteristics and medical comorbidities.